A First Branchial Cleft Cyst Masquerading as a Chronic Non-Healing Wound - Ng Syiao Wei; Aaron Wong Chun Chian; Aziah Ab Rani; Yoke Chin Mun; Jothi Shanmuganathan (Talenta Publisher, 2025)
Background: First branchial cleft anomaly exhibits variable clinical features, ranging from a painless swelling, discharging sinus or pit, to recurrent infection. It could be easily misdiagnosed and mismanaged, resulting in recurrence. Hence, any swellings or pits in Poncet’s triangle with a history of recurrent infection should raise the suspicion of a first branchial cleft anomaly. Objective: To present a case of chronic non-healing wound caused by an incompletely excised first branchial cleft anomaly. Methods: Case observation of a patient with a history of incomplete excision of a first branchial cyst. Results: Our patient was a case of incompletely excised first branchial cyst which subsequently presented as a chronic non- healing wound. She had undergone several workup for non-healing wound resulting in delay in receiving definitive treatment. Conclusion: Early recognition of first branchial cleft anomalies is important to prevent chronic complications and mismanagement.